Electrochemical behavior of lithium chromium oxide / Faezah Kassim - Kassim, Faezah (2012)
Cyclic Voltammetry (CV) is an electrochemical method which can be used to understand the basic electrochemistry of a reaction. The cyclic voltammetry tester is an instrument that controls the potential of the working electrode with respect to the reference electrode while also measuring the current flow between the working electrode and counter electrode. In CV, the potential of a working electrode is cycled linearly between two potential values at which the oxidation and reduction of a solute occurs. The resulting current-potential curve is called a cyclic voltammogram. This is a very useful technique and has several applications such as understanding the redox behaviour of a given molecule, mechanistic understanding of organic reactions, etc. In this study, the two sample of Lithium Chromium Oxide (LiCr02) with anneal at 650C and 850°C were tester in CV. After that the electrochemical behaviors of each sample were determined. The result of each sample is reversible reaction and the potential difference of LiCr0₂ with anneals at 650C and 850C is 3.0V and 2.87 V respectively. This result is approximately with theoretical difference potential value of LiCr0₂ and it shown the LiCr0₂ can be a good active electrode material inside Li-ion batteries.